Tangent modulus method – An original method to measure in-situ rock stress. (December 2018) - Fujii, Y.; Makasi, M.; Kodama, J.; Fukuda, D.; Goto, K.; Kumakura, S.; Kanaoka, M.; Dassanayake, A.B.N.
Abstract: This paper proposed Tangent Modulus Method (TMM) which is an improved oriented core method to determine in-situ rock stresses. In this approach, the cylindrical specimens prepared along different directions from thick core samples were uniaxially compressed twice to a given stress level. The stress value of the bending point in the first loading cycle of the stress-tangent modulus curve is considered as the normal component of the in-situ rock stress along the drilled direction of the specimen. Four types of rocks from soft porous tuff and sandstone to hard crystalline granite was investigated to evaluate the potential of this method. The effects of changes in strain rate, temperature, water content, confining and pore pressure, and stresses larger than the preload on the stress value of the bending point were experimentally investigated on preload specimens to investigate their influence on TMM. Comparison of the stress measurement results by TMM and an overcoring method at AK tunnel in Hokkaido, Japan was also performed to validate the TMM.